Not knowing you know: A new objection to the defeasibility theory of knowledge - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2015)
Foley (2012: 93–98) and Turri (2012: 215–19) have recently given objections to the defeasibility theory of propositional knowledge. Here, I give an objection of a quite different stripe by looking at what the theory must say about knowing that you know. I end with some remarks on how this objection relates to rival theories and how this might be a worry for some of these.